Penerapan Desain User Experience Pada Aplikasi Penghitungan Matematika Bagi Anak Penyandang Tunagrahita di Quali International Surabaya - Yohanes Hendra Wijaya; Liliana Liliana; Lily Eka Sari (Jurnal Infra, 2021)
Intellectual disability is a condition that happens to a child under 18 years old. This condition can lead to cognitive problems and below average intelligence. Because of this condition, those children need special care, especially for learning. One of the important lessons to learn is mathematics, because they need it to live in society. This research applies a design that focused on children with intellectual disability in an android application to learn mathematics. The design uses a simple, attractive, and interactive display so they don’t get confused or get bored easily. The materials used are adjusted to the competency standards for those children to suit their abilities. The application is designed to be an alternative teaching aid in mathematics. The results of this study are that children with intellectual disability can use 70.5% of the features of this application which are adjusted to their abilities. The application succeeded in helping children to improve their skills. According to the teachers at Quali International Surabaya, the material used in this application is in accordance with the needs of the children, and is delivered quite easily and clearly. Application is also suitable to be used as a teaching aid for mathematics lessons at school.